2022
DOI: 10.3390/vaccines10122116
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Baseline 25(OH) Vitamin D Levels and Both Humoral Immunity and Breakthrough Infection Post-COVID-19 Vaccination

Abstract: Objective: Vaccines against COVID-19 induce specific antibodies whose titer is perceived as a reliable correlate of protection. Vitamin D confers complex regulatory effects on the innate and adaptive immunity. In this study, we explored a plausible impact of baseline vitamin D content on achieved immunity following COVID-19 vaccination. Methods: A retrospective observational study comprising 73,254 naïve subjects insured by the Leumit Health Service HMO, who were vaccinated between 1 February 2020 and 30 Janua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 64 publications
2
7
0
Order By: Relevance
“…Unlike iron and zinc, serum concentrations of fat-soluble vitamins (A, D, and E) in our study displayed no significant association with either vaccine-specific antibody binding affinity or neutralizing ability against SARS-CoV-2 virus. This aligns with some existing research on COVID-19 vaccination,[21][22][23][24][25] but contrasts with others reporting positive associations between vitamin D and antibody responses [18][19][20]. These discrepancies might stem from variations in study populations, including pre-existing vitamin D status, vaccination schedules (primer vs. booster dose), vaccine type (inactivated vs. mRNA), and even participant age 23,24.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Unlike iron and zinc, serum concentrations of fat-soluble vitamins (A, D, and E) in our study displayed no significant association with either vaccine-specific antibody binding affinity or neutralizing ability against SARS-CoV-2 virus. This aligns with some existing research on COVID-19 vaccination,[21][22][23][24][25] but contrasts with others reporting positive associations between vitamin D and antibody responses [18][19][20]. These discrepancies might stem from variations in study populations, including pre-existing vitamin D status, vaccination schedules (primer vs. booster dose), vaccine type (inactivated vs. mRNA), and even participant age 23,24.…”
supporting
confidence: 78%
“…[14][15][16] Nine studies have reported the associations between serum vitamin D concentrations or status (sufficient, deficient, or insufficient) and humoral responses following COVID-19 vaccinations, yet inconsistent conclusions have been reached. [17][18][19][20][21][22][23][24][25] Investigations into the influence of micronutrients on antibody binding affinity and neutralizing capacity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), crucial parameters for immune protection, are virtually non-existent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The missing pieces of the puzzle within the complex framework of natural immunity are cellular immunity and other antibody types targeting multiple epitopes. In this regard, T cells seem to possess a pivotal role in SARS-CoV-2 protective immunity [ 38 , 39 ]. The advantage of targeting different immunogenic epitopes other than the spike protein during natural infection was reported before [ 40 , 41 ]; hence, targeting other immutable components of the viral structure, or multiple parts of the virus are emerging exciting avenues for vaccine optimization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have reported that native vitamin D supplementation protects against infectious diseases, particularly respiratory diseases 20 . In research on SARS-CoV-2 vaccination studies, several reports showed the association between 25OHD levels and SARS-CoV-2 IgG titers 21,22 . These studies reported that higher 25OHD levels were associated with higher SARS-CoV-2 IgG after vaccination.…”
Section: Discussionmentioning
confidence: 99%